2010
DOI: 10.1021/jp101243k
|View full text |Cite
|
Sign up to set email alerts
|

Pd@Pt Core−Shell Nanostructures with Controllable Composition Synthesized by a Microwave Method and Their Enhanced Electrocatalytic Activity toward Oxygen Reduction and Methanol Oxidation

Abstract: Three-dimensional Pd@Pt core−shell nanostructures with controllable shape and composition were synthesized by using a one-step microwave heating method. The nanostructures with the morphology, structure, and composition being easily controlled through adjusting the molar ratio between Pt and Pd precursor were characterized by transmission electronic microscopy (TEM), scanning electronic microscopy (SEM), X-ray powder diffraction (XRD), and energy-dispersive X-ray (EDX) techniques. In addition, the electrocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 59 publications
3
103
1
4
Order By: Relevance
“…7. The intense peak at around 0.05 V for Pd@Pt NDs/C was originated from the Pd surface uncovered by the porous Pt shell [26] and this peak was weakened gradually during the potential cycling, further confirming the dissolution of Pd. After 300 cycles, PdPt NCs are obtained, and that intense peak on the CV curve completely disappears.…”
Section: Electrocatalytic Performancesmentioning
confidence: 80%
See 1 more Smart Citation
“…7. The intense peak at around 0.05 V for Pd@Pt NDs/C was originated from the Pd surface uncovered by the porous Pt shell [26] and this peak was weakened gradually during the potential cycling, further confirming the dissolution of Pd. After 300 cycles, PdPt NCs are obtained, and that intense peak on the CV curve completely disappears.…”
Section: Electrocatalytic Performancesmentioning
confidence: 80%
“…(2 2 2) planes of the FCC structure of Pt and Pd, respectively. Because Pt and Pd possess the same crystal structure (FCC) and very close lattice parameter, the sets of diffraction peaks of Pt and Pd are overlapped [25,26]. The diffraction peaks of Pd@Pt NDs/C are sharper than that of Pt/C, indicating larger particle size and good crystallinity of Pd@Pt NDs.…”
Section: Physical Characterization Of Pd@pt Ndsmentioning
confidence: 99%
“…Microwave irradiation has been applied in the microwave-assisted synthesis of inorganic nanostructured materials, including metals [71][72][73], semimetals [74,75], alloys [73,76], metal oxides [77][78][79][80], metal sulfides [55,[81][82][83], and others [84,85].…”
Section: Microwave-assisted Methodsmentioning
confidence: 99%
“…20) [403,[406][407][408], and in the past few years, an enormous amount of studies related to Pd@Pt core-shell-structured catalysts for ORR have been conducted, and great efforts have been made to improve catalytic activities through controlling shell thicknesses, core sizes or morphologies. In terms of shell thickness, a monolayer is in theory ideal and has been elaborately achieved through the use of different methods including the UPD, the ALD and the sputtering deposition, exhibiting better catalytic activities for ORRs than pure Pt due to strain and ligand effects [45,59,65,66,299,301,304,334]. However, experimental results have indicated that optimum Pt thicknesses involve 2~3 atomic layers, rather than the monolayer for catalytic performances [297,299,409,410].…”
Section: Pd As Corementioning
confidence: 99%